Potenciali in perspektive rabe lesne biomase v Sloveniji - Krajnc, Nike (Gozdarski vestnik, 2011)
Wood biomass was and still is an important source of energy for households in Slovenia. Among all renewable sources of energy wood biomass prevails as the source for heat production. More than 75 % of wood biomass is used in households for apartment heating and cooking. Number of households using wood biomass has increased in the last 5 years. The share of renewable energy sources should reach 25 % by 2020. The government of Slovenia has prepared an Action plan for renewable sources of energy in summer 2010 in which ways to reach our targets are foreseen.
Keywords: biomasa; lesna biomasa; raba lesa; uvoz; izvoz; Slovenia; Slovenija